Disordered eating and insulin restriction in youths receiving intensified insulin treatment: Results from a nationwide population‐based study. Issue 2 (23rd September 2015) - Bächle, Christina; Stahl‐Pehe, Anna; Rosenbauer, Joachim
ABSTRACT: Objective: This Germany‐wide population‐based study sought to estimate the prevalence of disordered eating and insulin restriction (IR) among 819 youths aged 11–21 years with early‐onset type 1 diabetes (T1D) and a disease duration of at least 10 years. Methods: All respondents answered the five‐item SCOFF screening questionnaire for eating disorders (EDs) and reported on the frequency of IR and clinical outcomes. Screening for disordered eating was positive when more than two SCOFF items were answered affirmatively. Frequent IR was defined as IR occurring more than five times per week. Results: A total of 28.2%/9.2% of the female/male patients were SCOFF‐positive without IR and 4.2%/5.3% reported frequent IR but were SCOFF‐negative; 2.7%/1.9% screened positive for both disordered eating and IR. Patients with disordered eating, frequent IR, or both showed significantly worse glycemic control and partly more inpatient‐treated diabetic ketoacidoses than patients who screened negative. Discussion: Approximately one in three female and one in six male patients with early‐onset long‐duration T1D reported disordered eating and/or frequent IR. Because of their association with worse outcomes, both disordered eating and IR should be considered in T1D care irrespective of sex, age at onset, and diabetes duration. (Int J Eat Disord 2016; 49:193–198)